The Sustainable Development Goal 4 and the Impact Ranking: Quality Education in Portuguese Higher Education Institutions - Nogueiro, Teresa (2022)
Sustainability based on the Sustainable Development Goals (SDGs) is currently a relevant dimension for the competitiveness of Higher Education Institutions (HEIs). Portuguese HEIs will have, therefore, to adapt to the demands of the times and follow the Sustainable Development practices. Therefore, Quality Education is, then, a factor that allows HEIs to have competitive advantages, given that Education is a critical success factor for these institutions. Through a qualitative analysis of articles on the theme of Sustainability in Higher Education and the THE Impact Ranking platform, we tried to understand the impact that SDG 4 - Quality of Education has on Portuguese Higher Education Institutions, registered on this platform from 2019 to 2022. The main conclusion is that SDG 4 does not seem to be considered yet by Portuguese HEIs as a distinctive factor to obtain competitive advantage in the universe of HEIs.